Motor Unit Properties of the First Dorsal Interosseous in Chronic Stroke Subjects: Concentric Needle and Single Fiber EMG Analysis - Yao, Bo; Klein, Cliff S.; Hu, Huijing; Li, Sheng; Zhou, Ping (Frontiers in Physiology, 2018)
The purpose of this study was to better understand changes in motor unit electrophysiological properties in people with chronic stroke based on concentric needle electromyography (EMG) and single fiber EMG recordings. The first dorsal interosseous (FDI) muscle was studied bilaterally in eleven hemiparetic stroke subjects. A significant increase in mean fiber density (FD) was found in the paretic muscle compared with the contralateral side based on single fiber EMG (1.6 ± 0.2 vs. 1.3 ± 0.1, respectively, P = 0.003). There was no statistically significant difference between the paretic and contralateral sides in most concentric needle motor unit action potential (MUAP) parameters, such as amplitude (768.7 ± 441.7 vs. 855.0 ± 289.9 μV), duration (8.9 ± 1.8 vs. 8.68 ± 0.9 ms) and size index (1.2 ± 0.5 vs. 1.1 ± 0.3) (P > 0.18), nor was there a significant difference in single fiber EMG recorded jitter (37.0 ± 9.6 vs. 39.9 ± 10.6 μs, P = 0.45). The increase in FD suggests motor units of the paretic FDI have enlarged due to collateral reinnervation. However, sprouting might be insufficient to result in a statistically significant change in the concentric needle MUAP parameters. Single fiber EMG appears more sensitive than concentric needle EMG to reflect electrophysiological changes in motor units after stroke. Both single fiber and concentric needle EMG recordings may be necessary to better understand muscle changes after stroke, which is important for development of appropriate rehabilitation strategies. The results provide further evidence that motor units are remodeled after stroke, possibly in response to a loss of motoneurons.